Formation of different alumina phases and magnesium aluminate spinel during contact of molten AlSi7Mg0.6 alloy with mullite and amorphous silica. (January 2017) - Salomon, Anton; Zienert, Tilo; Voigt, Claudia; Dopita, Milan; Fabrichnaya, Olga; Aneziris, Christos G.; Rafaja, David
Graphical abstract: Highlights: Corrosion of mullite or fused silica coatings by molten AlSi7Mg0.6 alloy was studied. The results of microstructural analyses were verified by thermodynamic calculations. Mullite decomposed to silica and alumina, silica was reduced by the molten alloy. The products of the corrosion reaction are MgAl2 O4 spinel and alumina. In fused silica, metastable γ-Al2 O3 precedes thermodynamically stable corundum. Abstract: Corrosion of alumina-based metal melt filters functionalized by 3Al2 O3 ·2SiO2 or fused SiO2 was investigated using local chemical and microstructure analyses and thermodynamic calculations. Molten aluminium alloy AlSi7Mg0.6 was employed as corrosion medium. The aluminium alloy was melted in a Spark Plasma Sintering apparatus in order to avoid the melt flow. During the reaction with the AlSi7Mg0.6 melt, 3Al2 O3 ·2SiO2 partly decomposed, and Al2 O3 reacted with magnesium from the melt and with oxygen from SiO2 to MgAl2 O4 . Silicon precipitated in the aluminium alloy. For corundum functionalized by fused SiO2, metastable γ-Al2 O3 was detected additionally to the above phases for short reaction times.